O Programa de Transição da justiça do trabalho pós-moderna após o advento da nova competência material do ART. 114, I DA CR/88 (EC 45/2004): o bloco histórico do novo Direito do Trabalho entre a Desconstrução (Contrarreforma) e a Construção (Reforma) do Conceito de Relação de Trabalho no Limiar do Século XXI - Vinicius Moreira de Lima (2011)
The axle of the Reformation of the Labour Court in Brazil is based on the concept of labour relation. This contains the concept of employment relationship, that express only the phenomenon of the employment labour. The concept of labour relation is the mediate consequence of the process of flexible accumulation of capital, that restored the regressive modernization in the ways of formal subordination of the labour to the capital and determined the magnifying of the material ability of the Labour Court to process and to judge all the isuues referring to the manual and intellectual nonsalarial labour. The historical result in the new ways of formal subordination of the labour to the capital estimates the objectivation of a new social division of the capitalist labour, due to the neoliberal toyotist productive reorganization and subsequent dialectic of outsourcings and subcontractings of the monopolist capital. The solution of conflicts of labour relation, deriving of civil contracts of collaboration and similar contracts, is distinct of the employment relationship because this support itself in the normative hypothesis of the rescissions of employment contracts. However, if simulation of inexistence of employment relationship in written contracts of labour relation takes place, the Labour Court will correct the fraud immediately and will apply the law to the singular case. The vigorous growth of the capital-service and the Labour Court is the expressions of the advance of the unproductive labour in the capitalist society, non-value generator (antivalue) or the real wealth of the material process of production. This irrationality needs compensation in the labouring judiciary sphere, with the extension of the co-management in the administration of the justice and the reduction of its bureaucratic apparatus, everything with target to convert the time expense into functions of bureaucratic administration in effective increase of time expense in judgement for the parts. This reduction of the bureaucratic upright, by means of the synergy of the magnifying of the material ability of the Labour Court, estimates the democratization of the labouring judiciary device and its horizontal approach to its majority addressee: the workers. The economic crisis of the monopolist capital and its financial hegemonic fraction reached the labouring judiciary device immediately it colonized and it to the detriment of the labouring creditors. The immediate consequence of this settling is the reasonable duration of the working action at law, that implies in Objective Responsibility of the State for the delay in the judicial sentence, question that will have processed and judged by the Labour Court. The reform of legal education is essential to overcome the ideological resistances against the new concept of labour relation, to modify the forms of conscience of the involved professionals and to especially correct the serious practical defects of forensic that not only harm the State, but society as a whole.